2013
DOI: 10.1007/s11064-013-1099-8
|View full text |Cite
|
Sign up to set email alerts
|

Motor Function in MPTP-Treated Tree Shrews (Tupaia belangeri chinensis)

Abstract: The tree shrew, a new experimental animal model, has been used to study a variety of diseases, especially diseases of the nervous system. 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is the gold standard for toxin-based animal models of Parkinson's disease (PD) because MPTP treatment replicates almost all of the pathological hallmarks of PD. Therefore, in this study, the effects of MPTP on the motor function of the tree shrew were examined. After five daily injections of a 3 mg/kg dose of MPTP, the moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Rodent models are seldom used for chronic stress paradigms of human disease, whereas tree shrews are (43)(44)(45). Furthermore, tree shrews are finding a place in many models of human brain pathogenesis from mapping of neuropeptide distribution (46), models for opiate addiction (47) to drug target mining (48) and specific diseases such as Parkinson's disease (49). HSV infection was first reported in the tree shrew in 1978 by Darai et al, who studied the pathogenesis following intravenous, intraperitoneal, and subcutaneous infection (27).…”
Section: Discussionmentioning
confidence: 99%
“…Rodent models are seldom used for chronic stress paradigms of human disease, whereas tree shrews are (43)(44)(45). Furthermore, tree shrews are finding a place in many models of human brain pathogenesis from mapping of neuropeptide distribution (46), models for opiate addiction (47) to drug target mining (48) and specific diseases such as Parkinson's disease (49). HSV infection was first reported in the tree shrew in 1978 by Darai et al, who studied the pathogenesis following intravenous, intraperitoneal, and subcutaneous infection (27).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that the tree shrew ( Tupaia belangeri ) has a much closer phylogenetic affinity to primates than rodents do (Chen et al, ; Fan et al, ; Ma et al, ). Compared with rodents, the tree shrew has a more developed brain at both the neuroanatomical and the neurophysiological levels, higher homology of neuropeptidomics, similar drug target protein sequences and a higher resemblance to humans in terms of the expression profiles of genes associated with numerous neuropsychiatric disorders (Chen et al, ; Fan et al, ; Ma et al, ). However, the tree shrew has yet to be adopted as a preclinical animal model for studying METH‐induced behavioral sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…The tree shrew striatum exhibits striking similarities compared to that of primates (Ni et al, ; Rice, Roberts, Melendez‐Ferro, & Perez‐Costas, ). The tree shrew might, therefore, serve as an alternative model for studies of human striatal pathologies, such as Parkinson's disease (PD) (Ma et al, ). The tree shrew has been successfully used to study the structure and function of the brain (Casagrande, Harting, Hall, Diamond, & Martin, ; Day‐Brown et al, ; Familtsev et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The tree shrew has been successfully used to study the structure and function of the brain (Casagrande, Harting, Hall, Diamond, & Martin, ; Day‐Brown et al, ; Familtsev et al, ). Moreover, there are many antisera (such as those for neuropeptide Y (Ni et al, ), corticotropin‐releasing factor (Kozicz, Bordewin, Czeh, Fuchs, & Roubos, ), parvalbumin (Ni et al, )), pharmacological reagents (e.g., 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (Ma et al, ), amyloid‐beta peptide 1–40 (Lin et al, )), and disease models (such as those for depression (Pryce & Fuchs, ), hepatitis‐B‐virus infection (Yang et al, ), and glioblastoma (Tong et al, )) available for biomedical studies in the tree shrew.…”
Section: Introductionmentioning
confidence: 99%